Gene expression patterns regulating the seed metabolism in relation to deterioration/ageing of primed mung bean (Vigna radiata L.) seeds - Sharma, Satyendra Nath (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.